Preoperative staging of carcinoma of the bronchus: can computed tomographic scanning reliably identify stage III tumours?. Issue 10 (October 1994) - White, P G; Adams, H; Crane, M D; Butchart, E G
Abstract : BACKGROUND--The aim of preoperative computed tomographic (CT) assessment of patients with carcinoma of the bronchus is to stage the tumour accurately, and forewarn the surgeon of any possible local extrapulmonary extension of tumour in patients considered to have potentially resectable disease. The ability of CT scanning to differentiate between conventionally resectable lung cancer (TNM stages I and II), locally advanced but resectable lung cancer (TNM stage IIIa), and locally advanced but unresectable lung cancer (TNM stage IIIb) was determined in a group of patients accepted for surgery. METHODS--Computed tomographic scans of 110 patients who underwent thoracotomy for intended resection of carcinoma of the bronchus, including 52 cases with stage III and 58 cases with stage I or II disease, were reviewed and the CT features and radiological interpretations correlated with the surgical and pathological findings. RESULTS--Thirteen CT scans were judged not to have been of diagnostic quality: of the remaining 97 cases 45 had stage III lung cancer, of whom 30 had successful resections, and 52 had stage I or stage II tumours. There was no difference in the frequencies of CT observations--including contiguity of tumour and mediastinum or chest wall, apparent mediastinal or chest wall invasion, proximity of tumour to the carina, mediastinal nodal enlargement, pulmonary collapse or consolidation and pleural effusion--in patients with stage I/II disease and patients with stage III disease. Similar results were found when the same observations were compared in all patients with resected disease and those with unresectable tumour. Sensitivity and specificity of CT was 27% and 96% respectively for tumour unresectability, 50% and 89% for mediastinal invasion, 14% and 99% for chest wall invasion, and 61% and 76% for mediastinal nodal metastases. Only 19 of 45 stage III tumours were correctly identified as being stage III and resectable or unresectable. CONCLUSIONS--In patients being considered for thoracotomy for resection of lung cancer, CT scanning used as the sole method of staging is of limited value for differentiating between stage I/II and stage III tumours. Patients should not be denied the opportunity for curative surgery on the basis of equivocal CT signs.